Strategi Pemberdayaan Masyarakat Melalui Pengelolaan Bank Sampah Untuk Mendukung Pembangunan Berkelanjutan Di Kabupaten Pringsewu - Nugroho, Imam; Priyo Purnomo, Eko; Khairunnisa, Tiara (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2025)
As the waste problem grows in Pringsewu Regency, Lampung Province, management efforts are needed that are not only effective, but also involve active community participation. This research aims to examine community empowerment strategies through waste bank management as a step to support sustainable development. Using a qualitative descriptive approach and phenomenological methods, this research includes field observations, in-depth interviews and document analysis. The research results show that waste banks are able to increase public awareness and participation in waste management, starting from sorting, collecting, to recycling. Apart from reducing piles of unmanaged waste, this program provides economic benefits in the form of additional income from recycling, as well as positive social impacts such as increasing community solidarity. However, challenges in the form of a lack of supporting facilities and uneven public awareness need to be addressed immediately. This research confirms that collaboration between the community, government and other stakeholders is critical to stopping this program. With a more innovative and participatory approach, waste bank management can become an effective model for supporting sustainable development at the local level.